Computational Visual Media - Hu, Shi-Min
Computational Visual Media is a peer-reviewed open access journal published under the brand SpringerOpen. It publishes original high-quality research papers and significant review articles on novel ideas, methods, and systems relevant to visual media. Computational Visual Media publishes articles that focus on, but are not limited to, the following areas: •  3D visual media processing •  Classification and composition of visual media •  Cognition of visual media •  Content security for visual media •  Enhancement and re-rendering of visual media •  Geometric computing for images and video •  Interactive editing of visual media •  Machine learning for visual media •  Social media computing •  Understanding of visual media •  Visual media retrieval •  Visualization and visual analytics Other interdisciplinary research into visual media that combines aspects of computer graphics, computer vision, image and video processing, geometric computing, and machine learning is also within the journal's scope. This is an open access journal, published quarterly by Tsinghua University Press and Springer. The open access fees (article-processing charges) are fully sponsored by Tsinghua University, China. Authors can publish in the journal without any additional charges.  .